Performance Evaluation of a Feedback Based Dynamic Scheduler for 802.11e MAC - Gennaro Boggia; Pietro Camarda; Luigi Grieco; Saverio Mascolo; Marcello Nacci; Marco Marsan; Giuseppe Bianchi; Marco Listanti; Michela Meo (Quality of Service in Multiservice IP Networks, 2005)
IEEE 802.11 Wireless Local Area Networks (WLANs) are a fundamental tool for enabling ubiquitous wireless networking. Their use has been essentially focused on best effort data transfer because the basic access methods defined in the 802.11 standard cannot provide delay guarantees to real-time flows. To overcome this limitation, the 802.11e working group has recently proposed the Hybrid Coordination Function (HCF), which is an enhanced access method that allows service differentiation within WLAN’s. While the 802.11e proposal gives a flexible framework to address the issue of service differentiation in WLAN’s, it does not specifies effective algorithms to really achieve it. This paper compares the performance of standard access methods proposed by the 802.11e working group with a novel Feedback Based Dynamic Scheduler (FBDS), which is compliant to 802.11e specifications. Simulation results, obtained using the ns-2 simulator, have shown that FBDS guarantees bounded delays to real-time flows for a very broad set of network loads and packet loss probabilities, whereas, analogous algorithms proposed by the 802.11e working group fail in presence of high network load.